Using Quizizz as an Alternative Medium in Applying the Picture and Picture Type Cooperative Learning Model in English Subject to Increase Vocabulary Mastery for Primary School Students - Febrianti, Adila; Sari, Nadia Tiara Antik; Nurmaharani, Indah (Educational Studies and Research Journal, 2024)
The mastery of English vocabulary of VC class students at UPTD SDN 1 Citalang is still in the low category. This can be seen based on the data from the pre-test results which show the overall average score of students which is only ≥ 40. The efforts that can be made by researchers to solve these problems are by applying the Picture and Picture model assisted by Quizizz. The objectives of this study are: 1) Knowing the ability of English vocabulary mastery of students in grade V elementary school before using the Picture and Picture model assisted by Quizizz. 2) Knowing the ability of English vocabulary mastery of students in grade V elementary school after using the Picture and Picture model assisted by Quizizz. 3) To find out the effect of Picture and Picture model assisted by Quizizz on students' English vocabulary mastery ability in grade V elementary school. Picture and Picture learning model is a cooperative learning model that uses picture media. The Quizizz application functions as a medium to display images so that learning can adapt to digitalization. The research method used is pre-experiment. Based on the results of the study, the average score of mastery of English vocabulary obtained through the post-test increased to ≤ 75. Based on these results, it can be concluded that the Quizizz-based Picture and Picture learning model can improve the mastery of English vocabulary of students in class VC UPTD SDN 1 Citalang.